Determinants of Profitability of the Islamic Life Insurance Industry in Indonesia - Raissa Hafsari, Juliana; Mukhsin, Moh; Pardiansyah, Elif (Fakultas Ekonomi dan Bisnis Islam _ IAIN Sultan Amai Gorontalo, 2024)
The purpose of this study is to ascertain how economic growth and company-specific variables affect the profitability of Islamic life insurance in Indonesia. This study employed a quantitative approach using a descriptive methodology. The sampling technique used purposive sampling with a sample of 10 Islamic Life Insurance companies in Indonesia. The results of this study indicate that partially the leverage variable has a negative and significant effect on profitability. Premium growth variable has a positive and significant effect on profitability. The variables of company size, tangibility, liquidity, and economic growth have no effect on profitability. While simultaneously the variables of company-specific factors (company size, leverage, tangibility, premium growth, and liquidity) and economic growth have a significant effect on profitability.